Induction of Salt Tolerance in Basmati Rice (Oryza sativa L.) - Sajjad, M. Siddique (1990)
Seven relatively salt tolerant mutants were selecled from segregating populations (1\'12) Wider saline sodic conditions. Further testing of mutants under different salt stresses proved the superiority of one mutant namely RST-24. The mutant also proved its salt tolerance potential under both the gravel culture and saline-sodic field conditions. The mutant slightly surpassed parantal variety Basmati-370, for"length-breadth ratio (milled kernel), elogation ratio and gel consistence .They yield and yield components and other quality traits of mutants and parent unnder salt stress are also presented.